Improvement quality of Bligon goat sperm trough separation by albumen - Bintara, Sigit; Keman, Soenarjo; Sumadi, Sumadi; Agus, Ali (2010)
This experiments were conducted to evaluate the influence of different concentration of albumen gradient in sperm separation on sperm quality of Bligon goat. Semen from 8 heads male Bligon goats aged around 2 years was collected by artificial vagina with frequency of once in four days. Sperm separation was conducted with different albumen gradient. Medium I: 5% upper fraction and 10% lower fraction, medium II: 10% upper fraction and 30% lower fraction, and medium III:15% upper fraction and 45% lower fraction. The results showed sperm separation with different albumen gradient was significantly difference (P<0.01) on motility, viability, and abnormality of sperm, respectively. Sperm motility before separation and after separation on medium I, II and III upper fraction was 80.5; 82.1; 83.5 and 85.2%, lower fraction was 80.5; 86.1; 87.2 and 88.3% respectively. Sperm viability before separation and after separation on medium I, II and III upper fraction was 90.4; 93.6; 93.1 and 93.6%, lower fraction was 90.4; 86.1; 87.2 and 88.3% respectively. Sperm abnormality before separation and after separation on medium I, II and III upper fraction was 13.1; 11.2; 9.2 and 7.1%, lower fraction was 13.1; 6.1; 5.3 and 4.2% respectively. The conclusion of this study was that there was albumen gradient may be used for improve sperm quality by increase motility and viability and decrease abnormality